Kontrak Mudharabah Pada PT. Sarana Multigriya Financial Ditinjau Dari Fatwa Dewan Syariah Nasional Nomor 07/DSN-MUI/IV/2000 Tentang Mudharabah - Dewi, Nisrina Mutiara (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
Abstract:SMF is a secondary housing company that provides refinancing to Islamic banks. SMF financing aims to address housing finance mismatch funding issues in Islamic banks. The application of the contract to this cooperation is the mudharabah contract. With mudharabah contracts, the SMF and Islamic Banks can invest from the profit sharing ratio. The mudharabah contract application in this collaboration must comply with the Fatwa Council National Fatwa regulations NO: 07 / DSN-MUI / IV / 2000 regarding mudharabah financing. This study uses a qualitative method. The research technique used is content analysis and the research approach method is normative juridical. The data used are primary data taken from interviews and draft secondary data contracts, MUI fatwas, literature studies. The objects studied were the contract formation procedure, the contents of the contract, and the conformity of the contract to the Fatwa of the National Sharia Council NO: 07 / DSN-MUI / IV / 2000 concerning mudharabah financing. The results of this study can be concluded that the SMF procedure in providing financing to Islamic banks is very concerned about risk and analyzes the business feasibility of sharia banks and the suitability of the mudharabah agreement at the SMF on the National Sharia Council Fatwa NO: 07 / DSN-MUI / IV / 2000 in SMF in general with the MUI fatwa. However, in bearing losses and profit sharing ratio at the mudharabah contract in SMF, it is less in accordance with the National Sharia Council Fatwa NO: 07 / DSN-MUI / IV / 2000.Keywords: Contract, Mudharabah, MUI FatwaÂ Abstrak:SMF merupakan perusahaan sekunder perumahan yang memberikan refinancing kepada Bank Syariah. Pembiayaan SMF bertujuan untuk mengatasi masalah mismatch funding pembiayaan perumahan di Bank Syariah. Penerapan Akad pada kerja sama ini yaitu akad mudharabah. Dengan akad mudharabah, maka SMF dan Bank Syariah dapat berinvestasi dari nisbah bagi hasil. Aplikasi akad mudharabah dalam kerja sama ini harus mematuhi peraturan Fatwa Dewan Syariah Nasional NO: 07/DSN-MUI/IV/2000 tentang pembiayaan mudharabah. Penelitian ini menggunakan metode kualitatif. Teknik penelitian yang digunakan adalah conten analysis dan metode pendekatan penelitian adalah yuridis normatif. Data yang digunakan yaitu data primer yang diambil dari wawancara dan data sekunder draft kontrak, fatwa MUI, studi kepustakaan. Adapun objek yang diteliti adalah prosedur pembentukan akad, isi akad, dan kesesuaian akad pada Fatwa Dewan Syariah Nasional NO: 07/DSN-MUI/IV/2000 tentang pembiayaan mudharabah. Hasil penelitian ini dapat disimpulkan prosedur SMF dalam memberikan pembiayaan kepada bank syariah sangat memperhatikan risiko dan menganalisis kelayakan bisnis bank syariah dan kesesuaian akad mudharabah di SMF pada Fatwa Dewan Syariah Nasional NO: 07/DSN-MUI/IV/2000 di SMF pada umumnya sudah sesuai dengan fatwa MUI. Namun dalam menanggung kerugian dan nisbah bagi hasil pada akad mudharabah di SMF kurang sesuaiÂ Fatwa Dewan Syariah Nasional NO: 07/DSN-MUI/IV/2000.Kata Kunci: Kontrak, Mudharabah, Fatwa MUI